Generalized Elliott-Yafet theory of electron spin relaxation in metals: origin of the anomalous electron spin lifetime in MgB2 - Simon, F; Dóra, B; Murányi, F; Jánossy, A; Garaj, S; Forró, L; Bud'ko, S; Petrovic, C; Canfield, P C (Physical review letters, 2008)
The temperature dependence of the electron-spin relaxation time in MgB2 is anomalous as it does not follow the resistivity above 150 K; it has a maximum around 400 K and decreases for higher temperatures. This violates the well established Elliot-Yafet theory of spin relaxation in metals. The anomaly occurs when the quasiparticle scattering rate (in energy units) is comparable to the energy difference between the conduction and a neighboring bands. The anomalous behavior is related to the unique band structure of MgB2 and the large electron-phonon coupling. The saturating spin relaxation is the spin transport analogue of the Ioffe-Regel criterion of electron transport.